2012
DOI: 10.1177/1753193412461582
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of volar angulation and shortening in 5th metacarpal neck fractures: an inter- and intra-observer validity and reliability study

Abstract: Four methods for measuring volar angulation in 5th metacarpal neck fractures were tested for validity and reliability. Mid-medullary canal measurement in the lateral view (method MC-90) has previously been proven valid in a cadaveric study, hence used as a reference to test validity of the latter three. These three yielded a significant different mean fracture angle compared with MC-90, with only minor enhancement in reliability. Therefore, none of these three methods is recommended as a better standard method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
1
35
0
2
Order By: Relevance
“…Summarizing these studies, we measured dorsal angulation of the fifth metacarpal neck fracture on the oblique view with higher reliability, but we subtracted angulation of the contralateral uninjured side from the corresponding injured side to calculate true angulation. We found that the median dorsal angulation of the normal sides was 12°, which concurs with greater amounts of dorsal angulation on the oblique view as compared with the lateral view reported in previous studies [10,17].…”
Section: Radiographic Evaluationsupporting
confidence: 91%
See 1 more Smart Citation
“…Summarizing these studies, we measured dorsal angulation of the fifth metacarpal neck fracture on the oblique view with higher reliability, but we subtracted angulation of the contralateral uninjured side from the corresponding injured side to calculate true angulation. We found that the median dorsal angulation of the normal sides was 12°, which concurs with greater amounts of dorsal angulation on the oblique view as compared with the lateral view reported in previous studies [10,17].…”
Section: Radiographic Evaluationsupporting
confidence: 91%
“…Lamraski et al [10] reported the reliabilities of both views were substantial, but that the oblique view had slightly greater reliability and produced significantly higher readings of 10.8°(SD, 11.6°). Sletten et al [17] also found the reliabilities of the lateral and oblique views substantial, but the oblique view had slightly greater reliability and produced significantly higher readings of 9°. However, Leung et al [12] concluded that the lateral view showed only fair reliability (j = 0.21).…”
Section: Radiographic Evaluationmentioning
confidence: 94%
“…The ROM of fifth metacarpophalangeal joint was also recorded using a finger goniometer. The angulation was measured by the pronated oblique view of plain radiograph based on methods introduced and advocated in previous reports1213. Briefly, the distal line was drawn from the mid-medullary point in the distal fragment to the most distal point of the metacarpal head, and the proximal line centrally through the shaft medullary canal, irrespective of where the line hit the basis of the metacarpal (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All patients (515) above 18 years referred with little finger metacarpal neck fractures were registered consecutively and assessed for eligibility ( Figure 1). Radiographs of both hands were standardized by the use of plexi glass devices for 30° oblique pronated and lateral radiographs in addition to the anteroposterior radiographs with supinated hand (Frere et al, 1982;Sletten et al, 2012a). Palmar angulation was measured using mid-medullary lines in the lateral view (method Medullary Canal-lateral; MC-90) (Sletten et al, 2012a).…”
Section: Trial Design and Participantsmentioning
confidence: 99%